Investigation of innovative thermochemical energy storage processes and materials for building applications - Aydin, Devrim (2016)
In this study, it is aimed to develop an innovative thermochemical energy storage system through material, reactor and process based investigations for building space heating applications. The developed system could be integrated with solar thermal collectors, photovoltaic panels or heat pumps to store any excess energy in the form of heat for later use. Thereby, it is proposed to address the problem of high operational costs and CO2 emissions released by currently used fossil fuel based heating systems in buildings. The aim of the study has been achieved by investigating and evaluating five of the following aspects: • Investigation of the feasibility of building integrated solar driven THS system under cold and mild climates, • Synthesis, characterization and physical experimentation of novel composite sorption energy storage materials • Development and investigation of a modular laboratory scale sorption reactor that use embedded air diffusers inside the sorbent for improving the energy storage density • Development and investigation of a full- scale modular solar driven THS system • Development and investigation of a heat pump driven sorption storage heater using multi-layer fixed bed sorption reactor These works have been assessed by means of computer simulation, laboratory and field experimental work and have been demonstrated adequately. The key findings from the study confirm the potential of the examined technology. Initially, a comprehensive review on thermal energy storage, with the aim of investigating the latest advancements on THS systems was performed. A comparative analysis on applicability of different heat storage methods for short term and seasonal heat storage under climate conditions in the UK, was also carried out. Results showed that short term heat storage is not a feasible option in the UK due to the very limited solar radiation. For the case of seasonal heat storage, it was found that, each 1 m3 of THS can provide averagely 14% of monthly (October to March) heating demand of a 106 m2 building, whereas LHS and SHS can provide 6% and 2% respectively. Later on, a range of candidate composite sorption materials were synthesized and characterized. Based on the applied characterization techniques, it was found that Vermicuilite-CaCl2 (SIM-3a) has excellent Ed coupled with good EMC and temc with its TGA analysis also suggesting significant mass loss in the working range 30 < T < 140 °C. Physical experimentation of the developed materials in a small scale custom test rig was also performed and in accordance with the characterization results, SIM-3a displayed the best hygrothermal and cyclic performance. These findings suggested that SIM-3a has very good potential for use in an open THS system. Upon completion of the material based studies, a 3kWh laboratory scale novel reactor using perforated pipes embedded inside the heat storage material was developed. The overall energy density of the reactor using SIM-3a was found 290 kWh/m3. Based on the obtained encouraging results, same concept was up scaled to a modular 25 kWh sorption pipe heat storage and similar energy density was achieved. Following the experimental work, theoretical analysis of the THS potential in Mediterranean climate conditions is conducted with a case study of the Island of Cyprus. The analysis results showed that the required heat storage volume to fully compensate heating demand of a domestic building in winter (December to February) is 5.25 m3 whilst the time required for charging the THS material with 8 m2 solar air collectors is slightly more than a month. The economic and environmental analyses results showed that payback period of the solar driven THS is 6 years whilst total CO2 emissions savings over 25 years lifetime is 47.9 tonnes. In order to validate the applicability of THS in Cyprus, a small prototype of integrated sorption pipe-solar concentrator was also developed and tested for room heating. It was found that adsorbent could be regenerated with solar energy during winter day time to be utilized at night for space heating. Study results also showed that sorption pipe with a heat storage volume of 0.017 m3 could meet up to 87% of the daily heat demand of a 12.4 m2 building. In order to validate the performance of the laboratory tested THS material and concept, a real scale (1000 kWh) modular solar driven THS system was developed based on the interpretation of the obtained theoretical, numerical and experimental data in earlier stages of the study. The preliminary testing on the prototype showed that each of four reactors could discharge a total of 248 kWh of thermal energy with an average thermal power of 4.8 kW. Additionally it is found that, in direct solar heating mode, transpired solar collectors used in the system could also generate daily total of 17 kWh thermal energy for the average solar intensity of 0.3 kW/m2. In the final stage of the study, a heat pump driven sorption storage heater was developed and investigated. The developed system performance was assessed with 5 different adsorption materials and under different operating conditions. The study results showed that Sim-3a and Vermiculite–(LiCl-CaCl2) (Sim-3cl) has the best hygrothermal performances and hygro-cyclic efficiencies. According to study results, COPs varies in the range of 1→2 depending on sorption materials properties and system operating conditions.